The impact of rotator cuff deficiency on structure, mechanical properties, and gene expression profiles of the long head of the biceps tendon (LHBT): Implications for management of the LHBT during primary shoulder arthroplasty. Issue 8 (13th May 2015) - Kurdziel, Michael D.; Moravek, James E.; Wiater, Brett P.; Davidson, Abigail; Seta, Joseph; Maerz, Tristan; Baker, Kevin C.; Wiater, J. Michael
ABSTRACT The long head of the biceps tendon (LHBT) occupies a unique proximal intra‐articular and distal extra‐articular position within the human shoulder. In the presence of a rotator cuff (RC) tear, the LHBT is recruited into an accelerated role undergoing potential mechanical and biochemical degeneration. Intra‐articular sections of the LHBT were harvested during primary shoulder arthroplasty from patients with an intact or deficient RC. LHBTs were stained (H&E, Alcian Blue) and subjected to histologic analysis using the semiquantitative Bonar scale and measurement of collagen orientation. LHBTs (n = 12 per group) were also subjected to gene‐expression analyses via an RT2‐PCR Profiler Array quantifying 84 genes associated with cell‐cell and cell‐matrix interactions. LHBTs (n = 18 per group) were biomechanically tested with both stress‐relaxation and load‐to‐failure protocols and subsequently modeled with the Quasilinear Viscoelastic (QLV) and Structural‐Based Elastic (SBE) models. While no histologic differences were observed, significant differences in mechanical testing, and viscoelastic modeling parameters were found. PCR arrays identified five genes that were differentially expressed between RC‐intact and RC‐deficient LHBT groups. LHBTs display signs of pathology regardless of RC status in the arthroplasty population, which may be secondary to both glenohumeral joint arthritis and the additional mechanical role of the LHBT in this population. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1158–1164, 2015.